Analisis Keabsahan Kuasa Hukum Non Muslim: Studi Kasus Perceraian di Pengadilan Agama Bandung - Ilhamuddin Qasim (Prodi Ahwal Syakhsiyah, Fakultas Syariah, Institut PTIQ Jakarta, 2021)
Lack of public understanding of how to proceed in court is an opportunity for advocates as legal advisors. This study aims to determine the role of non-Muslim advocates who handle divorce cases at the Bandung City Religious Court. Research with this qualitative method by conducting observations, collecting data and information about advocates who have proceedings in the Religious Courts. The results of this study indicate that non-Muslim advocates in handling divorce cases at the Bandung Religious Court have limited roles, not all things can be done by non-Muslim advocates when the advocate is running a divorce case even though the advocate already has a power of attorney.